L’arte del processo nella narrativa di Anna Banti - Rivetti, Sonia (Incontri. Rivista europea di studi italiani, 2024)
The art of the trial in Anna Banti’s narrative Starting from a series of works by the Italian writer Anna Banti, the aim of this essay is to carry out a thematic analysis around the theme of the narrative ego in the different declinations that it takes − real but also fictional or merely psychological − specifically within the trial form. Starting from the novel Artemisia (1947), subsequently connecting to the theatrical gestation that Anna Banti herself wanted to attribute to the theme of the debate in Corte Savella (1959), and then going back to the other two works, respectively Il bastardo (1953) and Insufficienza di prove ( 1975), the study aims to give evidence and concreteness to the drama and intrinsic psychological tension of the different characters represented, but with an explicit reference, ultimately, to the figure of the narrator herself. Conclusively, through the story La signorina (1975), this time in a form not directly connected to the trial theme, we intend to show how the trial of the various characters is oriented towards a trial of one’s own ego.